Insulin degludec overdose in an adolescent with type 1 diabetes: proactive management including monitoring using the Freestyle Libre flash glucose monitoring system. (1st June 2018) - Thompson, Harmony; Lunt, Helen; Fleckney, Cate; Soule, Steven
Summary: An adolescent with type 1 diabetes and a history of self-harm, which included intentional overdoses and insulin omission, presented with an insulin degludec overdose. She had been commenced on the ultra-long-acting insulin, degludec, with the aim of reducing ketoacidosis episodes in response to intermittent refusal to take insulin. Insulin degludec was administered under supervision as an outpatient. Because it was anticipated that she would attempt a degludec overdose at some stage, the attending clinicians implemented a proactive management plan for this (and related) scenarios. This included long-term monitoring of interstitial glucose using the Abbott Freestyle Libre flash glucose monitor. The patient took a witnessed overdose of 242 units of degludec (usual daily dose, 32 units). She was hospitalised an hour later. Inpatient treatment was guided primarily by interstitial glucose results, with capillary and venous glucose tests used as secondary measures to assess the accuracy of interstitial glucose values. Four days of inpatient treatment was required. The patient was managed with high glycaemic loads of food and also intermittent intravenous dextrose. No hypoglycaemia was documented during the admission. In summary, while a degludec overdose may require several days of inpatient management, in situations where proactive management is an option and the dose administered is relatively modest, it may be possible to avoid significant hypoglycaemia. In addition, this case demonstrates that inpatient interstitial glucose monitoring may have a role in managing insulin overdose, especially in situations where the effect of the insulin overdose on glucose levels is likely to be prolonged. Learning points: Degludec overdoses have a prolonged effect on blood glucose levels, but if the clinical situation allows for early detection and management, treatment may prove easier than that which is typically needed following overdoses of a similar dose of shorter acting insulins. Inpatient real-time interstitial monitoring helped guide management, which in this context included the prescription of high dietary carbohydrate intake (patient led) and intravenous 10% dextrose (nurse led). Use of inpatient interstitial glucose monitoring to guide therapy might be considered 'off label' use, thus, both staff and also patients should be aware of the limitations, as well as the benefits, of interstitial monitoring systems. The Libre flash glucose monitor provided nurses with low cost, easy-to-use interstitial glucose results, but it is nevertheless advisable to check these results against conventional glucose tests, for example, capillary 'finger-stick' or venous glucose tests.